Engagements étudiants en Algérie post-22 février. Sociohistoire d’un mouvement « désenchanté » - Siham Beddoubia (L’Année du Maghreb)
As soon as the hirak broke out, Algerian students have been mobilizing across the country: on the first Tuesday after 22 February, students were the first to take to the streets in support of the hirak's claims. This gave rise to a tradition known as "Student Tuesdays", which marked the beginning of the structuring of the hirak through various categories of activists calling for an end to the current regime. During the first months of the hirak, these students, whether or not they were members of existing student organisations, actively participated in the Tuesday and Friday marches. They put forward the same popular demands as the "Friday protesters". These students chanted anti-system slogans, organised strikes and rejected several of the government's initiatives to end the crisis. The structure of this movement appears to be closely linked to struggles that predate 22 February, and it seems to be following on from issues that have not yet been resolved, such as those of 2011 in the context of the Arab revolutions, but also much earlier (rejection of the LMD system, student autonomy, regime change, etc.). This text looks back at the involvement of students in the hirak from 22 February 2019, with a focus on the Rassemblement des étudiants libres d'Oran. The primary aim is to go beyond the euphoric analyses focused on the massive scale of the hopeful student marches, which have been put forward by several observers of the student hirak. We need to try and understand the ins and outs of this movement from below. The weakening of the movement as a result of repression in the pre- and post-election context of 12/12 and the restrictions on gatherings due to the coronavirus pandemic raise questions about the effects of continuity/discontinuity and mobilisation/demobilisation within the student hirak.Continuous observation of the marches and in-depth discussions with several of the movement's protagonists have highlighted a number of observations. This text highlights two phases of the student hirak. Firstly, national history was a unifying element: the students seemed to want to take part in writing the national novel; they drew on the rhetoric of memories and history through slogans, songs linked to the national movement and symbols of the war of national liberation. In this way, there was a real desire to reinvest the field of struggle and revitalise demands around the issue of democracy. The second phase was more complex, because the hirak in general very quickly imposed the need for dialogue and the first divisions emerged around the issue of representation, but also on the ideological dilemma. Indeed, several currents of thought were at odds within the movement. The students were led to question their ideological affiliations (Islamist, “pagsiste”, far left, close to the government). For many of them, their family socialisation explains their biographical availability, particularly through a presentation of the history of Algeria that differs from an official history that tends to obscure certain components of the National Movement. The initial cohesion around a national symbolic repertoire is thus confronted with the ideological and political cleavages that existed before 22 February, in which the students struggle to find their place, or at least seem disenchanted by the overall situation. We still have to think about their future as activists...